'ALMOST TOO RUINOUS TO BE REPAIRED': THE UNKNOWN TREASURES PROJECT AT THE NATIONAL ARCHIVES AND THE COURT OF COMMON PLEAS BREVIA FILES. Issue 136 (April 2018) - Mascio, Adalgisa
Abstract : In nearly 700 years of activity the position of the Court of Common Pleas in the English legal scene was paramount. This article examines the court's surviving brevia files, recently accessioned into series CP 52 at The National Archives. It unravels their archival journey from their creation by the court's clerks through centuries of neglect and often poor storage conditions up to the digital world of The National Archives online catalogue, with a focus on variation and change in the court's record keeping practice over time. It also outlines the complex task of arranging and cataloguing the files so that they could be made available to researchers.